2015
DOI: 10.1109/jmems.2015.2429675
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Flexible and Disposable Microneedle-Fluidic-System With Finger-Driven Drug Loading and Delivery Functions for Inflammation Treatment

Abstract: Patch-based transdermal drug delivery technology offers a convenient way to administer drugs without the drawbacks of standard hypodermic injections related to issues, such as patient acceptability and injection safety. In this paper, we developed a flexible and disposable microneedle-fluidicsystem (MFS), which can achieve finger driven on-chip drug loading and delivery functions by integrating polydimethylsiloxane-based microfluidic dispensing networks, check valves, micropump, and SU-8 microneedles in a patc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 61 publications
1
14
0
Order By: Relevance
“…In the healthcare area, we have experienced the widespread use of electrochemical biosensors in centralized clinical tests, performed in controlled environments and laboratories, followed by point-of-care portable sensors, such as the glucose sensor strip introduced in the 1980s, and recent trends toward wearable and implantable electrochemical sensors capable of real-time on-body diagnosis. This evolution has brought us many advances toward the prevention, management, and treatment of diseases as well as new materials and technologies. Important features of these modern sensors are the ability to conform to the body and various other curved surfaces and high integration of miniaturized multiparameter sensors. The development of microscale flexible electrochemical devices has allowed the rapid uprise of implantable sensors and sensor integrated medical devices, such as a medical wire, a medical needle, an endoscope, etc. Implantable sensors are strong candidates for next-generation enzyme sensors, with glucose monitoring devices, employing implantable needles, receiving tremendous attention toward continuous blood glucose measurements.…”
mentioning
confidence: 99%
“…In the healthcare area, we have experienced the widespread use of electrochemical biosensors in centralized clinical tests, performed in controlled environments and laboratories, followed by point-of-care portable sensors, such as the glucose sensor strip introduced in the 1980s, and recent trends toward wearable and implantable electrochemical sensors capable of real-time on-body diagnosis. This evolution has brought us many advances toward the prevention, management, and treatment of diseases as well as new materials and technologies. Important features of these modern sensors are the ability to conform to the body and various other curved surfaces and high integration of miniaturized multiparameter sensors. The development of microscale flexible electrochemical devices has allowed the rapid uprise of implantable sensors and sensor integrated medical devices, such as a medical wire, a medical needle, an endoscope, etc. Implantable sensors are strong candidates for next-generation enzyme sensors, with glucose monitoring devices, employing implantable needles, receiving tremendous attention toward continuous blood glucose measurements.…”
mentioning
confidence: 99%
“…It is widely used in electronic skin, neurogrid and robotic hand [ 14 , 15 , 16 , 17 ]. Additionally, NiTi is applied in the fields of sensors and actuators, e.g., in E-capsules, micro-needles, and bladder actuators [ 9 , 18 , 19 ]. Shape memory composites are transformed by applying an external force at a high temperature, and the shape is temporarily fixed when it cooled.…”
Section: Introductionmentioning
confidence: 99%
“…It has been challenging to integrate additional functions into such silicon-based 3dimensionally fabricated arrays. Therefore, there have been few studies on multifunctional needle-type arrays reported thus far 32,33 . Abaya et al introduced an optrode array for infrared neural stimulation 34,35 , which is a rare example of studies integrating additional functions into this needle-type electrode array.…”
Section: Introductionmentioning
confidence: 99%